STRATEGI KOMUNIKASI BERBASIS NEW MEDIA DISKOMINFO KAB. MUKOMUKO PROVINSI BENGKULU SEBAGAI MEDIA INFORMASI PEMBANGUNAN - Armansyah Armansyah (JURNAL ILMIAH SYI'AR, 2018)
Communication is a series of activities conveying messages so that feedback is obtained from receiving messages. This also applies to the secretarial public relations department of Communication and Information in Mukomuko District. It must pay attention to how the information is packaged and can be communicated well so that the public or the community can receive the information validly. The success of effective communication activities is largely determined by determining communication strategies. On the other hand, if there is no good communication strategy, the effect of the communication process is not impossible to cause negative effects.The research conducted was descriptive research. This study describes the data in the form of responses from research subjects to upload communication strategies the department of Communication and Information of Mukomuko regency in delivering programs to the community. The Department of Communication and Information Service in Muko-Muko showed that the delivery of information to the public began to enter the digital era. This is also indicated by the existence of information that can be easily obtained by the public such as including on the website or media that makes it easy for people to access. In addition, the information conveyed by Communication and Information Service in Mukomuko regency can be accepted by the public in general so that the community can play an active role in providing input or suggestions regarding to the program of the development of Mukomuko.